COMPETITIVE STRATEGY OPTIMIZATION IN THE ACCOMMODATION SERVICES INDUSTRY USING THE SWOT AND STP APPROCHES - Rahardja, Rico Prasetyo; Khalid , Zulvia (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study examines competitive strategy within industrial environments through the Analysis of STP, SWOT Analysis and Porter's Five Forces framework. The study aims to provide a comprehensive understanding of how these strategic tools can be integrated to enhance competitive advantage. This study provides a fundamental viewpoint on strategic positioning by employing SWOT analysis to identify external opportunities and threats in addition to internal strengths and weaknesses. By emphasising market segmentation, targeting, and positioning tactics catered to particular client demands, the STP strategy further refines this. At last, Porter's Five Forces model is utilised to evaluate the industry's competitive dynamics by examining elements like the risk of new competitors, the ability of suppliers and buyers to negotiate, the possibility of replacement products, and the intensity of competition. Through a comprehensive analysis of various frameworks, the journal suggests a comprehensive approach for businesses to successfully traverse intricate industrial contexts and maintain a competitive edge.